Evaluation of Vibration Effects of Massage Machines on Muscles Fatigue - Zhongliang Yang; Yumiao Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Automated massage machines have been widely used in family for the past few years, but there was limit scientific evidence to support for them positive effects. This paper aims to evaluate the massage effects on recovery of muscle fatigue and explore the optimal massage machine design parameters. Two subjects participated in prone bridge exercises to make the erector spinae muscles fatigue before and after massage at six levels of speed. The surface electromyography (sEMG) signals were recorded from erector spinae muscles only during PB exercises. The vibration velocity of beat massage and subjective massage comfort (SMC) were measured at six massage speed. Based on the test data, empirical models were established between vibration velocity, sEMG and SMC. Results indicated that vibration velocity of beat massage had a significant impact on sEMG and SMC. This represents the positive effects of the massage machine on recovery of post-exercise local muscles fatigue. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4486